Ocular Surface Integrity, Dry Eye Signs and Symptoms in Wearers of Coloured Soft Contact Lenses from Different Sources: A Pilot Study - Mohamad, Hilman Muqriez; Badarudin, Noor Ezailina; Zahari, Ilyanon; Hajar Maidin, Mohamad Hanif (International Journal of Allied Health Sciences, 2024)
Background: This study explored the effects of wearing coloured soft contact lenses (CL), sourced from both optometry and non-optometry providers, on ocular surface integrity and dry eye signs and symptoms. Methods: Five participants were randomly assigned to wear a pair of contact lenses from one of the two sources for one month, followed by a one-month washout period, after which they switched to lenses from the other source. Ocular surface integrity was assessed through measurements of tear meniscus height (TMH), non-invasive keratograph tear film breakup time (NIKBUT), and tear breakup time (TBUT) at three intervals: during the initial visit, one week postwear, and one month post-wear. Additionally, participants completed the Contact Lens Dry Eye Questionnaire-8 (CLDEQ-8) at the one-week and one-month follow-up visits to evaluate dry eye status. Repeated measures ANOVA was used to analyse changes in ocular surface integrity over the one-month period, while paired sample t-tests were conducted to assess changes in CLDEQ-8 scores between the one-week and one-month follow-ups. Results: The repeated measures ANOVA showed no significant differences in TMH, NIKBUT, or TBUT between the two types of contact lenses over the one-month period (p > 0.05). Similarly, paired samples t-tests revealed no significant changes in CLDEQ-8 scores between the base line, one-week and one-month follow-up visits (p > 0.05). Conclusion: The study concluded that there were no significant differences in ocular surface integrity or dry eye symptoms between coloured soft contact lenses obtained from optometry and nonoptometry sources after one month of wear.